Association of overexpression of PLD6, CHRAC1 and PDCD5 with type 2 diabetes mellitus - Ali Adel Dawood; Zayd Kays Omer; Alyaa Farouk Al-Omari (Medicinski glasnik, 2024)
Aim: Diabetes type 2 (DT2) is a metabolic disease characterized by high blood sugar caused by insulin resistance and/or insufficient insulin production. The pathogenesis of DT2 is complicated by both genetic predisposition and environmental and lifestyle variables. At least 150 genetic variants have been linked to the probability of having DT2. The aim of this study was to determine the expression of PLD6, CHRAC1, and PDCD5 genes in type 2 diabetic patients. Methods: Information on 12 DT2 patients was obtained from the Gene Expression Omnibus (GEO) using the series identification (ID) (GSE34008). The analysis tools GEO2R, String Utils (STRING), University of Alabama at Birmingham Cancer data analysis (UAL-CAN), and the Cancer Genome Atlas (TCGA) were used. The human protein atlas provided details on gene cancer. Results: Only ten genes with expression differences ranging from low to high were selected. PLD6, CHRAC1, and PDCD5 were detected to have higher expression in patients compared to controls. The number of patients with primary pancreatic adenocarcinoma for SLC16A4, DERK2, and CHRAC1 was greater than that of healthy controls. Concerning the severity of cancer, all chosen genes demonstrated a greater proportion of affected individuals compared to the control group. Conclusion: There are multiple genes whose increased expression is linked to type 2 diabetes.
Keywords: ꞵ -cells; diabetes; gene; GEO